Highly concentrated and stable few-layers graphene suspensions in pure and volatile organic solvents. (March 2016) - Azani, Mohammad-Reza; Hassanpour, Azin; Carcelén, Veronica; Gibaja, Carlos; Granados, Daniel; Mas-Ballesté, Ruben; Zamora, Felix
Graphical abstract: Highlights: Easy procedure to prepare stable few-layers graphene suspensions in organic volatile solvents. Conductive glasses graphene coated with different levels of transparency. Few-layers graphene stable suspensions. Graphene coating of surfaces. Spray-on graphene suspensions. Abstract: Highly stable graphene suspensions in pure organic solvents, including volatile solvents such as ethanol, tetrahydrofurane, chloroform, acetone or toluene have been prepared by re-dispersion of a graphene-powder. Such re-dispersable solid is produced by precipitation or solvent elimination from graphene suspensions obtained by sonication of graphite in several organic solvent–water mixtures. Re-dispersion is feasible in a wide range of pure organic solvents, obtaining high quality few-layers graphene flakes stable in suspension for months. As a proof-of-concept, on-glass spray deposition of some of these suspensions, e . g . ethanol or tetrahydrofuran, results on electrically conductive transparent coatings. These results suggest industrial potential use of the scalable technology here developed to fabricate low-cost devices with many different potential applications.